At the edge of chaos: a prospective multiple case study in Australian general practices adapting to COVID-19. Issue 1 (18th January 2023) - Russell, Grant; Lane, Riki; Neil, Jennifer; Advocat, Jenny; Sturgiss, Elizabeth Ann; Staunton Smith, Timothy; Alexander, Karyn; Hattle, Simon; Crabtree, Benjamin F; Miller, William L
Abstract : Objectives: The rapid onset and progressive course of the COVID-19 pandemic challenged primary care practices to generate rapid solutions to unique circumstances, creating a natural experiment of effectiveness, resilience, financial stability and governance across primary care models. We aimed to characterise how practices in Melbourne, Australia modified clinical and organisational routines in response to the pandemic in 2020–2021 and identify factors that influenced these changes. Design: Prospective, qualitative, participatory case study design using constant comparative data analysis, conducted between April 2020 and February 2021. Participant general practitioner (GP) investigators were involved in study design, recruitment of other participants, data collection and analysis. Data analysis included investigator diaries, structured practice observation, documents and interviews. Setting: The cases were six Melbourne practices of varying size and organisational model. Participants: GP investigators approached potential participants. Practice healthcare workers were interviewed by social scientists on three occasions, and provided feedback on presentations of preliminary findings. Results: We conducted 58 interviews with 26 practice healthcare workers including practice owners, practice managers, GPs, receptionists and nurses; and six interviews with GP investigators. Data saturation was achieved within each practice and across the sample. The pandemic generated changes to triage, clinical care, infection control and organisational routines, particularly around telehealth. While collaboration and trust increased within several practices, others fragmented, leaving staff isolated and demoralised. Financial and organisational stability, collaborative problem solving, creative leadership and communication (internally and within the broader healthcare sector) were major influences on practice ability to negotiate the pandemic. Conclusions: This study demonstrates the complex influences on primary care practices, and reinforces the strengths of clinician participation in research design, conduct and analysis. Two implications are: telehealth, triage and infection management innovations are likely to continue; the existing payment system provides inadequate support to primary care in a global pandemic.